2010
DOI: 10.1002/chem.201001032
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Molecular Understanding of Cation–Anion Interactions—Probing the Electronic Structure of Imidazolium Ionic Liquids by NMR Spectroscopy, X‐ray Photoelectron Spectroscopy and Theoretical Calculations

Abstract: Ten [C(8)C(1)Im](+) (1-methyl-3-octylimidazolium)-based ionic liquids with anions Cl(-), Br(-), I(-), [NO(3)](-), [BF(4)](-), [TfO](-), [PF(6)](-), [Tf(2)N](-), [Pf(2)N](-), and [FAP](-) (TfO=trifluoromethylsulfonate, Tf(2)N=bis(trifluoromethylsulfonyl)imide, Pf(2)N=bis(pentafluoroethylsulfonyl)imide, FAP=tris(pentafluoroethyl)trifluorophosphate) and two [C(8)C(1)C(1)Im](+) (1,2-dimethyl-3-octylimidazolium)-based ionic liquids with anions Br(-) and [Tf(2)N](-) were investigated by using X-ray photoelectron spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
336
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(358 citation statements)
references
References 89 publications
(156 reference statements)
22
336
0
Order By: Relevance
“…S3. The N(1s) binding envelope of the quaternised films could be fitted to a main nitrogen environment at 401.9 ± 0.1 eV corresponding to two equivalent nitrogen centres in positively charged imidazolium rings [39,51,52], Fig. 3 and Scheme 1.…”
Section: Palladium-poly(ionic Liquid) Catalyst Membranementioning
confidence: 98%
“…S3. The N(1s) binding envelope of the quaternised films could be fitted to a main nitrogen environment at 401.9 ± 0.1 eV corresponding to two equivalent nitrogen centres in positively charged imidazolium rings [39,51,52], Fig. 3 and Scheme 1.…”
Section: Palladium-poly(ionic Liquid) Catalyst Membranementioning
confidence: 98%
“…Using X-ray photoelectron spectroscopy [ok? ], it has been demonstrated that the ionic liquid anion can affect q i on the cation (Cremer et al, 2010). In addition, EXAFS spectroscopy with hard X-rays has been used to study structure in ionic liquids (Hartley et al, 2014, Migliorati et al, 2015.…”
Section: Figurementioning
confidence: 99%
“…Recent work by several groups [30][31][32][33][34][35][36][37][38][39][40][41][42][43] including those of the authors [44][45][46][47][48][49][50][51][52][53][54][55][56][57] shows that a rigorous surface science approach can indeed be applied to IL surfaces and interfaces. There are mainly two aspects, which make such studies possible: First, the vapor pressure of many aprotic ILs is suffi ciently low so that their surfaces can be straightforwardly studied under ultrahigh vacuum (UHV) conditions.…”
Section: Introductionmentioning
confidence: 99%